Pemanfaatan Media Pembelajaran Komik untuk Meningkatkan Hasil Belajar pada Mata Pelajaran IPS Jenjang SMP - Erliana Dwi Mutiara; Desy Safitri; Sujarwo (PT. PENERBIT TIGA MUTIARA, 2024)
Abstract To improve Social Sciences (IPS) learning outcomes, interesting learning media such as comics are needed which are the focus of research. The research will examine how the use of comics as learning media can influence student learning outcomes. This research uses literature studies to collect and analyze various appropriate data related to the use of comics in social studies learning in junior high schools. The research results show that the use of comic media improves student learning outcomes, especially in social studies learning compared to the use of other learning media. Apart from learning outcomes, student motivation also increases significantly in social studies learning because comics make it easier for students to understand the information in them.